Spectrum of neurological disorders admitted in Tribhuvan University Teaching Hospital Maharajgunj - Gajurel, BP; Parajuli, P; Nepali, R; Oli, KK (Journal of Institute of Medicine Nepal, 2013)
Introduction: Neurologic disorders are very common. Data on the type and burden of neurological cases either in the outpatient and inpatient settings in our country are not available. This research has been done to perform a descriptive analysis of the spectrum of neurological cases which were admitted over a period of one fiscal year in Tribhuvan University Teaching Hospital (TUTH), Maharajgunj, Kathmandu Methods: This retrospective study included all patients who were admitted with any neurological complaints over a period of one fiscal year (Shrawan 2067 B.S. to Asar 2068 B.S). Results: The total number of patients admitted was 1165. Out of these, 693 cases were due to neurological disorders (59.48%). The most common disorders were stroke, seizure disorder and central nervous system infections. Conclusion: A variety of neurological disorders, from very common to very rare, were admitted. DOI: http://dx.doi.org/10.3126/joim.v34i3.8918 Journal of Institute of Medicine, December, 2012; 34:50-53